OPTIMAL TREATMENT OF HYDRONEPHROSIS IN CHILDREN - Allaev M.Y.; Gafurov A.A.; Abduvaliyeva Ch.M.; Nazirov N. (Scholar Express Journals, 2024)
Hydronephrosis may be nonobstructive and may not require surgical treatment. Corrected hydronephrosis is also common. This is when the kidney still does not contract after repair of the pelvic-ureteric segment, the dilated calyxes remain wide enough, but urine flow is restored. This is often the case when a kidney with very poor function is operated on. The main thing we are fighting for is not to narrow the pelvis, but to restore the outflow from the kidney. In such cases it is sometimes necessary to perform a second operation when the child grows up
Keywords: hydronephrosis; surgical treatment; kidney